Prototype of an Arduino-Based 3D Scanner Printed Using 3D Printing - Ikhwan Taufik; Elvanes Betel Bangun; Raka Mahendra Sulistiyo; El Vionna Laellyn Nurul Fatich (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2024)
Three-dimensional (3D) scanning technology is pivotal in manufacturing, product design, and architecture, enabling precise digital reconstructions of real-world objects. However, existing 3D scanners are often costly and complex, hindering accessibility. To address this, our study presents a cost-effective 3D scanning system using Arduino technology. Utilizing an Arduino Nano, GP2Y0A21YK0F IR Sensor, stepper motors, motor drivers, and an SD card module, our system offers a simple solution for scanning small objects and creating 3D models. The scanner measures object distance, rotates a work table, and captures scan data, processed with MeshLab software. Successful scanning demonstrates affordability and automation. Future work will focus on optimizing accuracy and scanning speed.